2017
DOI: 10.1049/iet-map.2016.1060
|View full text |Cite
|
Sign up to set email alerts
|

Direct metal laser sintering process investigation: application to 3D slotted waveguide antennas

Abstract: Increasing demand for the development of multifunction radio‐frequency‐systems requires the fabrication of complex architectures. Three‐dimensional (3D) direct metal printing direct metal laser sintering (DMLS) has the required properties to build complex and robust parts. To determine whether this technology is able to replace traditional machining methods, it needs to be extensively examined. In the present study, several waveguides operating in a wide‐frequency range, and slotted waveguide antennas with rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Aluminum (AlSi7Mg0.6) and titanium (Ti6Al4V) rectangular waveguides were fabricated with additive manufacturing. Their transmission losses were found to be two times higher than simulated values at X-band (8-12 GHz) and Ka-band (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) [1,2]. For a copper (CuSn15) rectangular waveguide fabricated with AM, its transmission loss at the V-band (40-75 GHz) was four times bigger than that produced by machining [3].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Aluminum (AlSi7Mg0.6) and titanium (Ti6Al4V) rectangular waveguides were fabricated with additive manufacturing. Their transmission losses were found to be two times higher than simulated values at X-band (8-12 GHz) and Ka-band (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) [1,2]. For a copper (CuSn15) rectangular waveguide fabricated with AM, its transmission loss at the V-band (40-75 GHz) was four times bigger than that produced by machining [3].…”
Section: Introductionmentioning
confidence: 84%
“…Braunisch et al [9] calculated an attenuation constant to account for propagation loss due to rough and smooth conductors. Martin-Guennou et al [35] showed that in a very rough as-built additive manufactured surface with quadratic surface mean roughness of RSq = 32 μm, surface roughness significantly contributed to transmission loss in the K and Q bands. In this study, the average surface roughness of as-built LBM surfaces of four waveguides ranges from 7 to 12 μm Ra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment on planar and conformal 1D and 2D resonant SWAs is presented in [47]. Several orientations and machine settings were studied to obtain consistent parts with high detail resolution and quality.…”
Section: Slotted Antennasmentioning
confidence: 99%
“…For the case of the SWA array, the RF performances are sensitive to dimensional variations from manufacturing, particularly the size of resonant coupling irises placed between the radiating waveguides and the feeding network [9]. These iris dimensions are difficult to control when using the DMLS manufacturing process [10,11], and no post-process or adjustment is possible inside the structure. The use of the TE20 mode to feed substrate integrated waveguide (SIW) travelling wave antennas or SIW slot arrays has already been described [12][13][14], but SIW SWA arrays suffer from dielectric losses and greater dispersion than air-filled devices [15].…”
Section: Of 11mentioning
confidence: 99%